Claiming power over life religion and biotechnology policy. - Hanson, Mark J. (Washington Georgetown university press, 2001)
Developments in biotechnology, such as cloning and the decoding of the human genome, are generating questions and choices that traditionally have fallen within the realm of religion and philosophy: the definition of human life, human vs. divine control of nature, the relationship between human and non-human life, and the intentional manipulation of the mechanisms of life and death. In "Claiming Power over Life", eight contributors challenge policymakers to recognize the value of religious views on biotechnology and discuss how best to integrate the wisdom of the Christian and Jewish traditions into public policy debates. Arguing that civic discourse on the subject has been impoverished by an inability to accommodate religious insights productively, they identify the ways in which religious thought can contribute to policymaking. Likewise, the authors challenge religious leaders and scholars to learn about biotechnology, address the central issues it raises, and participate constructively in the moral debates it engenders. This book will be of value to policymakers, religious leaders, ethicists, and all those interested in issues surrounding the intersection of religion and biotechnology policy.
Acknowledgments Introduction Mark J. Hanson Meaningful Resistance : Religion and Biotechnology Courtney Campbell Human Cloning and Liberal Neutrality : Why We Need to Broaden the Public Dialogue B. Andrew Lang The Uneven Playing Field of the Dialogue on Patenting John H. Evans Religious Voices in Biotechnology : The Case of Gene Patenting Mark J. Hanson Religious Perspectives on Biotechnology : Theological Interpretations of Biotechnology : Issues and Questions Ronald Cole-Turner Religion, Biotechnology, and the Integrity of Nature : Critical Examination Gerald P. McKenny Jewish Views on Technology in Health Care Elliot N. Dorff Contributors Index
Keywords: Biotechnology -- Religious aspects; Medical technology -- Religious aspects; 241.63*5 -- Theologische ethiek: bio-ethiek (bioethiek); genetische experimenten; transplantatie; eugenetica